2020
DOI: 10.1093/police/paaa057
|View full text |Cite
|
Sign up to set email alerts
|

Taking an Evidence-Based Approach to Evidence-Based Policing Research

Abstract: A growing body of international evidence reflects the increasing recognition of evidence-based policing (EBP) and the co-production of research, yet the extent of which such research is being implemented remains unclear. This study seeks to explore the efficacy of EBP in relation to practical implementation issues and assess the impact research is having on practice, both within and external to a specific Constabulary. Twenty-nine research studies, conducted in association with the Constabulary, were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Several interviewees discussed the need for strategic co-ordination of primary research with many highlighting the process ad hoc , and often not focused on force priorities. Police leadership should ensure a clear strategy and pathway for effective dissemination of research findings to those in the organisation tasked with improving policy and practice (Nutley et al, 2002; Boulton, 2020). It was evident from the interviews and focus groups that there was no such mechanism in place.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Several interviewees discussed the need for strategic co-ordination of primary research with many highlighting the process ad hoc , and often not focused on force priorities. Police leadership should ensure a clear strategy and pathway for effective dissemination of research findings to those in the organisation tasked with improving policy and practice (Nutley et al, 2002; Boulton, 2020). It was evident from the interviews and focus groups that there was no such mechanism in place.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The opportunities to the service of adopting EBP through the utilisation of a range of methodological approaches, moving beyond the original ideas of high quality and rigorous experimental design proposed by Sherman (1998), have often been discussed (Brown et al , 2018; Boulton et al , 2020). This isn't to ignore the need for research rigour, but rather embrace the many and varied approaches available to the new constables within the limitations imposed by their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based policing, like evidence-based medicine, confronts a stubborn implementation barrier. One recent study found that only about half of EBP projects generated a change in practice or policy (Boulton et al, 2021).…”
Section: Implementing Fundamental Changementioning
confidence: 99%